Impact Of Digital Marketing On Key Accounts Business Performance With Mediating Role Of Market Sensing And Customer Linking Capabilities - Ishfaq Ahmad , Dr. Fahad Khan Afridi , Dr. Kashif Amin , Abdur Rehman (Migration Letters, 2024)
Key accounts are the vital businesses which are strategically beneficial for the companies. Due to the limitation of resources and integration issues most of the key accounts businesses have often faces an obstacle in establishing and maintaining the digital marketing capabilities. There exist little studies that specifically examine the relationship between digital marketing capabilities (DMCs) and key account business performance (KABP). Therefore, the objectives of the study are (a) to assess the effect of DMCs on marketing sensing capabilities (MSCs), customer linkage capabilities (CLCs) and KABP, (b) to assess the effect of MSCs and CLCs on KABP (c) to assess the mediating effect of MSCs and CLCs in the relationship between DMCs and KABP. To examine the aforementioned objectives, the researcher chose a positivist research philosophy and used a deductive research technique. The researcher used a survey research technique with a sample of three hundred eighty-nine executives and managers working i[1]n the eight major electronics distribution businesses in Pakistan. Using stratified random sampling with proportional allocation, the sample size was ascertained. A significant response rate was obtained by using a survey questionnaire to gather data. The research used multivariate analysis method to evaluate construct validity, factor analysis, suggested measurement models, and structural equation modeling (SEM), via AMOS software. The statistical findings revealed that (a) the DMCs has a significant positive effect on MSCs, CLCs and KABP, (b) MSCs, and CLCs have a significant positive effect on KABP, (c) MSCs, and CLCs mediates between DMCs and KABP. This report emphasizes the crucial role that plays in improving important account performance, offering firms enlightening information as they navigate the dynamic business context.